Chicken coccidiosis in peri-urban family farming in two South American countries : prevalence and circulating eimeria spp. - Tomazic, Mariela Luján; Britez, Jesica Daiana; Pisón-Martínez, María Luz; Barbano, Pablo Martin; Canet, Zulma Edith; Trangoni, Marcos David; Poklepovich Caride, Tomás Javier; Cubas, Facundo; Alegría-Morán, Raúl; Ramírez-Toloza, Galia; Rodriguez, Anabel Elisa (MDPI, 2025)
Family poultry production systems (FPPSs) in Chile and Argentina produce high-quality and nutritious food. However, little is known about chicken coccidiosis in these production systems. This work aimed to determine the Eimeria sp. positivity rate, circulating species, general farm management, and knowledge of the disease in FPPSs by gaining access to peri-urban markets in these two countries. The overall Eimeria sp. positivity rate, determined in 88 fecal samples, was 85.1%. Oocysts per gram in Argentinean meat-producing FPPSs were significantly higher than in Argentinean and Chilean egg-producing FPPSs. Multiplex-PCR based on seven Eimeria spp. Sequence-Characterized Amplified Region (SCAR) markers showed a great diversity of circulating species, with E. mitis (70.3%), E. acervulina (62.2%), and E. tenella (59.5%), followed by E. maxima (43.2%), E. praecox (32.4%), E. necatrix (18.9%), and E. brunetti (5.4%). Low awareness among family producers and low implementation of control measures were found. Importantly, pathogenic species were found even in asymptomatic chickens, which represents a potential chicken health threat. Furthermore, the administration of sulfonamides to broilers with clinical signs poses a risk of environmental contamination. This is the first comprehensive cross-sectional study showing that Eimeria sp. is a persistent parasite in peri-urban FPPSs in Argentina and Chile.